A creativity-led rural renaissance? Amenity-led migration, the creative turn and the uneven development of rural Australia - Argent, Neil; Tonts, Matthew; Jones, Roy; Holmes, John (Elsevier Ltd, 2013)
This paper explores the relationships between amenity, creativity, internal migration processes and economic development in a significant proportion of rural Australia. In developing a predictive and synoptic model of migration attractiveness, we explore the extent to which rural regions and localities have been able to attract ‘creative’ human capital since 2001, the geographic distribution of such gains, and the extent to which ‘creative class’ presence is positively associated with business and employment growth. We find that ‘creative industry’ members find high amenity and high socio-economic status areas of rural Australia attractive places in which to live and work, yet this group's presence is not readily attributable to rural migration processes. Presence of the creative class, together with select rural amenity indicators, are powerful predictors of firm numbers but appear to have little influence over employment creation in rural Australia. Given these findings, the paper argues that building regional development policies around the attraction of the creative class is unlikely to yield major economic development gains.